WACANA PENANDA KEKOHESIAN DAN KEKOHERENSIAN DALAM BERITA COVID-19 DI LIPUTAN6.COM - Zulfa Nur Maulida (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study analyzes cohesion and coherence in covid-19 news in the June 2020 liputan6.com edition. The purpose of this study is to describe the markers of cohesion and coherence of news discourse in online media with the June 2020 edition of Covid-19. This study aims to describe the discourse markers of cohesion and coherence in the Covid-19 news on the June 2020 edition of Liputan6.com. Looking for markers of cohesion and coherence in the news. Based on the results of data analysis found several things as follows. First, markers of grammatical cohesiveness by using reference markers, substitution, ellipsis, and conjunctions. Second, markers of lexical cohesion which include antonymy, hyponymy, and collocation. Third, the markers of coherence are found as "signified" coherence. Markers of "tagged" coherence include additive coherence, chronological coherence, causality coherence, and contrast coherence. On the basis of the results of data analysis, it can be concluded as follows. First, the mark of cohesiveness in the covid-19 news on Liputan6.com in the June 2020 edition generally uses explicit cohesion markers. Second, the grammatical cohesive markers used include references, substitution, ellipsis, conjunctions, and lexical cohesive markers used include antonym, hyponym, and collocation. Third, the markers of the coherence of co-19 news in the June 2020 edition generally use "tagged" coherence, such as additive coherence, chronological coherence, causality coherence, and contrast coherence